CARDIOVASCULAR COMPLICATIONS IN INTRA-ABDOMINAL HYPERTENSION (LITERATURE REVIEW) (Journal of Universal Science Research, 2024)
This article focuses on cardiovascular complications associated with intraabdominal hypertension (IAH), a critical condition that can lead to severe systemic consequences. The pathophysiological mechanisms linking IAH to cardiovascular dysfunction are analyzed, emphasizing the effects of increased intra-abdominal pressure on hemodynamics, cardiac output, and vascular resistance. Particular attention is given to the role of IAH in the development of conditions such as myocardial ischemia, arrhythmias, and other cardiovascular disorders. The article also highlights diagnostic challenges and management strategies for mitigating cardiovascular risks in patients with IAH. Recommendations for further research and clinical practices are proposed to improve outcomes for affected patients